Pengaruh Pemberian Pakan Dedak Padi Terfermentasi Cairan Rumen terhadap Kualitas Fisik Daging Ayam - Rahmaniar Abdia; Djalal Rosyidi; Irfan Djunaidi (Faculty of Animal Science Universitas Brawijaya, 2017)
The purpose of this research was to determine the effect of fermented rice bran fermented with rumen fluid addition in feed on physical quality of broiler meat. The material used in this research was 20 broiler chest meats taken from broiler that weren’t differentiated by gender and maintained for 35 days. The research was done by feeding trial designed with Complete Randomized Design (CRD) with 5 treatments and 4 replications consisting of P0: basal feed (mixture of concentrate, rice bran, and yellow corn), P1: basal feed and rice bran fermented with rumen liquid 2.5%, P2: basal feed and rice bran fermented with rumen liquid 5%, P3: basal feed and rice bran fermented with rumen liquid 7.5%, and P4: basal feed and rice bran fermented with rumen liquid 10%. If there was a difference between treatments, tested by Duncan’s Multiple Range Test (DMRT). The variables measured were meat tenderness, pH, and water holding capacity (WHC). The results of this study indicated that the addition of rice bran fermented with rumen liquid in broiler feed showed significantly different effect on meat tenderness P3 (24.43±1.78), P2 (23.18±3.32), P4 (21.73±2.51), P1 (20.25±5.34), and P0 (15.60±3.62), but not showed significantly different effect on pH P0 (5.61±0.09), P4 (5.57±0.01), P3 (5.56±0.01), P2 (5.50±0.01), and P1 (5.45±0.09), and WHC P2 (62.05±8.03), P4 (60.87±5.18), P1 (60.19±14.62), P0 (59.45±4.15), and P3 (54.48±3.52). It could be concluded that feed with the 7.5% level of rice bran fermented with rumen liquid (P3) in broiler feed showed the best results on physical quality of broiler meat.